Chemisorption of NCO on Cu(1 0 0): A density functional theory study - Garda, Graciela Raquel (2005)
The isocyanate group adsorption on sites of different coordination of Cu(1 0 0) was theoretically studied considering the cluster approach. The site of four-fold symmetry is the most favored. When NCO adsorbs on Cu, it charges negatively. This electron transfer from the substrate is greater for the site of lowest coordination. The projected DOS curves for the most important valence molecular orbitals of isocyanate group indicate a strong mixing between its 2π orbital and 3dxz and 3dyz AOs of Cu. The predicted asymmetric mode at 2187 cm-1 for NCO adsorbed on the hollow site agrees very well with the experimental observed values of 2162-65 cm -1. © 2005 Elsevier B.V. All rights reserved.